2018
DOI: 10.1186/s12936-018-2325-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasmodium relictum, a cosmopolitan agent of avian malaria

Abstract: BackgroundMicroscopic research has shown that Plasmodium relictum is the most common agent of avian malaria. Recent molecular studies confirmed this conclusion and identified several mtDNA lineages, suggesting the existence of significant intra-species genetic variation or cryptic speciation. Most identified lineages have a broad range of hosts and geographical distribution. Here, a rare new lineage of P. relictum was reported and information about biological characters of different lineages of this pathogen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 108 publications
2
32
2
Order By: Relevance
“…3). Similar intraspecific variations have been reported in the relatively well-studied morphospecies Haemoproteus majoris [59], Plasmodium relictum [60] and other avian haemosporidians, in which morphologically defined species are known to consist of multiple closely related cytb lineages. While there have been a few reports of H. larae in gulls, these reports are all solely based on morphological identification [61], and future investigation using a combination of molecular and morphological methods may reveal other molecular lineages of H. larae.…”
Section: Discussionsupporting
confidence: 78%
“…3). Similar intraspecific variations have been reported in the relatively well-studied morphospecies Haemoproteus majoris [59], Plasmodium relictum [60] and other avian haemosporidians, in which morphologically defined species are known to consist of multiple closely related cytb lineages. While there have been a few reports of H. larae in gulls, these reports are all solely based on morphological identification [61], and future investigation using a combination of molecular and morphological methods may reveal other molecular lineages of H. larae.…”
Section: Discussionsupporting
confidence: 78%
“…Most notable are the major extinctions of the endemic bird population of Hawaiian honeycreepers (Fringillidae, subfamily Carduelinae) [7, 9]. Plasmodium relictum is the most successful malaria parasite worldwide, and is reported from over 300 avian species belonging to 11 orders [10]. Studies on experimentally infected birds found the P. relictum lineage GRW4 and the related species P. elongatum to be highly virulent for naïve hosts [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmodium relictum is a well-known parasite of birds and is considered to be one of the world's top 100 most invasive species (Alowe et al 2000;Valkiūnas et al 2018). The morphologically defined species P. relictum consists of several cryptic lineages based on absolute differences in the mitochondrial gene cytochrome b, and the most prevalent lineage is SGS1 (Palinauskas et al 2007;Hellgren et al 2009Hellgren et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Closely related to SGS1 is the P. relictum lineage GRW4 (Valkiūnas et al 2007(Valkiūnas et al , 2018, which also encompasses a broad host range of 80 bird species spanning five orders (Beadell et al 2006;Bensch et al 2009). When identified in the blood of wild birds, GRW4 normally displays low parasitemia and seems in general to be quite avirulent with little or no fitness consequences for the host (Bensch et al 2007;Asghar et al 2011;Dimitrov et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation